Comparing Open and Robotic Unilateral Transversus Abdominis Release in Incisional Hernias With a Lateral Component: A Single Center Retrospective Study - Stijn Van Hoef; Stijn Van Hoef; Hasan H. Eker; Frederik Berrevoet; Mathias Allaeys (Journal of Abdominal Wall Surgery)
IntroductionLateral hernias are often more challenging to correct when compared to midline defects, due to the anatomic boundaries of the bony pelvis, retroperitoneum, and costal margin. With the insurgence of robot assisted abdominal wall surgery, these defects have been found more manageable through a minimal invasive repair. In this study, we aim to present our short-term results of incisional hernia repair with a lateral component requiring a unilateral transversus abdominis release, through open surgery versus robot assisted.MethodsA retrospective analysis was performed of our robotic and open abdominal wall repairs of lateral hernias, where a unilateral transversus abdominis release was performed, between January 2017 and December 2023. Patient, hernia and perioperative details are reported.Results54 patients in the open group versus 10 patients in the robotic group were included. Hernia width and hernia surface area were higher in the open group, but not significant. Operation time was similar between open and robotic procedures. In-hospital complications, surgical site infection and clinical seroma rate during the first 30 postoperative days were similar in both groups. There was a clear difference in length of stay, in favor of the robotic group.DiscussionIn our limited series, a robotic approach seems safe and feasible when faced with large lateral hernias. Short-term results show a shorter length of stay using the robotic approach, with no significant difference in short term complications, specifically SSI-rate. However, conclusions are limited due to the low number of patients and additional studies should be performed to account for long term recurrence and increase included patient number.